2013
DOI: 10.1177/1043659613503873
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Incontinence Among Emirati Women With Diabetes

Abstract: Clinicians working with Emirati diabetic women should endeavor to enhance screening for incontinence and design culturally appropriate strategies for teaching and treating this complication of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…Mixed incontinence was the most prevalent type of UI occurring in 238 (95.2%) of our participants. Furthermore, studies with diabetic and non-diabetic participants also reported higher prevalence of urinary incontinence with diabetic than non-diabetic women [18]. The co-morbidity of type two diabetes mellitus in all our participants might have contributed to their having such high prevalence of stress incontinence and urge incontinence/OAB.…”
Section: Prevalence Of Ui In Kuwaiti Women With Dmmentioning
confidence: 47%
See 4 more Smart Citations
“…Mixed incontinence was the most prevalent type of UI occurring in 238 (95.2%) of our participants. Furthermore, studies with diabetic and non-diabetic participants also reported higher prevalence of urinary incontinence with diabetic than non-diabetic women [18]. The co-morbidity of type two diabetes mellitus in all our participants might have contributed to their having such high prevalence of stress incontinence and urge incontinence/OAB.…”
Section: Prevalence Of Ui In Kuwaiti Women With Dmmentioning
confidence: 47%
“…The findings were that stress incontinence and urge incontinence symptoms were present in 197 (56.3%) and 208 (59.4%) respectively. In this study, the co-morbidity was type 2 diabetes mellitus and the duration of diabetes was the most significant risk factor for incontinence [18]. A Bahrani study [19], investigated the risk factors in 259 women receiving treatment for UI at the Urogynecologic clinic, at Salmaniya Medical complex, Bahrain, Their findings revealed the following risk factors for UI: recurrent urinary tract infection 34%, chronic constipation 32%, DM 17.4%, spinal diseases 14.3%, gastrointestinal diseases 12%, neurological diseases 2%, bronchial asthma and chronic obstructive pulmonary disease 4.6% and the remaining 17% were on diuretics [19].…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations